1987
DOI: 10.1128/aac.31.2.164
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and in vivo susceptibility of the Lyme disease spirochete, Borrelia burgdorferi, to four antimicrobial agents

Abstract: The antimicrobial susceptibility of Borrelia burgdorferi isolated from human spinal fluid was determined in vitro and in vivo. A broth dilution technique was used to determine the MBCs of four antimicrobial agents. The Lyme disease spirochete was most susceptible to ceftriaxone (MBC, 0.04 ,ug/ml) and erythromycin (MBC, 0.05 ,ug/ml), then tetracycline (MBC, 0.8 ,ug/ml), and finally penicillin G (MBC, 6.4 ,g/ml). Syrian hamsters were used to determine the 50% curative doses (CD_0s) of the four antimicrobial agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
1
2

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 18 publications
(31 reference statements)
5
91
1
2
Order By: Relevance
“…Cognizant of these results and that of a treatment study of Brucella infection in mice (12), Bockenstedt et al increased the dose of doxycycline to 50 mg/kg twice daily (8). The MIC of doxycycline for the N40 strain of B. burgdorferi used by Bockenstedt et al has not been reported, but for other strains of B. burgdorferi, MICs of doxycycline are typically 4-to Ͼ10-fold higher than the 0.06-g/ml MIC of doxycycline for the strain of Brucella melitensis in the study relied upon by Bockenstedt et al (19,23). Furthermore, 100% of the mice were cured of the Brucella infection with a 45-day course of doxycycline (50 mg/kg twice daily), whereas a 21-day course of therapy was less effective and a 30-day course of treatment was not attempted (12).…”
Section: Study By Hodzic Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Cognizant of these results and that of a treatment study of Brucella infection in mice (12), Bockenstedt et al increased the dose of doxycycline to 50 mg/kg twice daily (8). The MIC of doxycycline for the N40 strain of B. burgdorferi used by Bockenstedt et al has not been reported, but for other strains of B. burgdorferi, MICs of doxycycline are typically 4-to Ͼ10-fold higher than the 0.06-g/ml MIC of doxycycline for the strain of Brucella melitensis in the study relied upon by Bockenstedt et al (19,23). Furthermore, 100% of the mice were cured of the Brucella infection with a 45-day course of doxycycline (50 mg/kg twice daily), whereas a 21-day course of therapy was less effective and a 30-day course of treatment was not attempted (12).…”
Section: Study By Hodzic Et Almentioning
confidence: 99%
“…Studies of the effects of antibiotic therapy in animals infected with B. burgdorferi have been conducted most often with mice (8,18,25,30,31,35,38,53,54) but also with hamsters (21,22), gerbils (15,32,42), dogs (48,49), and nonhuman primates (39). In most of the studies the animals were immunocompetent, but in several the animals were immunocompromised (25,37,48).…”
Section: Animal Studies: General Remarksmentioning
confidence: 99%
“…The microaerophilic character of the borrelia is indicated by its preference for the bottom portion of the culture medium during initial growth (11,92). Addition of low concentrations (0.1 to 0.2%) of agarose to further thicken the medium improves the recovery of B. burgdorferi from animal fluids and tissues (4,6,94,95). In some cases reducing agents, such as L-cysteine, dithiothreitol, and superoxide dismutase, have been added as supplements.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In one published study, hamsters were used to assess the efficacy of different antimicrobial agents on B. burgdorferi (94). The (29,135).…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Lyme disease is a multistage disease which has been divided into 3 stages, defined by different clinical features and duration after infection (11,27,28). Since Lyme disease has been a serious social problem in North America and Europe, susceptibilities of Borrelia related to Lyme disease against various antibiotics have been examined for development of successful treatment (1,5,6,9,10,14,15,(25)(26)(27).…”
mentioning
confidence: 99%